The Frequency & Determinants of the Use of Nutritional Supplements and Hormones among Selected Gym Users in Karachi, Pakistan - Azhar, Nida; Ahmer, Zaeema; Naqvi, Umm-e-Rabab (Nurture, 2022)
Purpose: The use of hormones/ anabolic androgenic steroids (AAS) and nutritional supplements (NS) has gained popularity worldwide for improving physical appearance and sports performance. There have been limited studies that examine the frequency and determinants of their use among gym users in Pakistan. Our objective was to estimate the frequency of NS and AAS consumption among gym users of Karachi and to determine the determinants of NS and AAS consumption. Methodology: An analytical cross-sectional study was conducted on 435 gym users from five districts of Karachi using non-probability quota sampling and gyms were selected on a convenience basis. Data were collected on a pre-tested validated tool and the association of outcome with variables was assessed by applying multivariate logistic regression using Statistical Package for the Social Sciences (SPSS) version 20.0. Findings: The frequencies of AAS and NS were 9.2% (n=40) and 42.5% (n=185) respectively. Reasons for use included increasing muscle size and strength, impressing the opposite gender, getting popularity on TikTok videos, and getting a boyfriend/girlfriend. Male gender (p=0.000) and gym users who were businessmen were more inclined to using hormones (p=0.033). Gym users of district Central were less likely to consume AAS (p =0.004). Contribution to literature and practical implications: The study concludes that male gender and occupation are positively associated with NS consumption and the dwelling of gym attendees is also significantly associated with AAS intake. These findings can help policymakers to make decisions for improvement in addressing public health issues.